Ideology and Palliative Care: Moral Hazards at the Bedside - Rhodes, Rosamond (Cambridge quarterly of healthcare ethics, 2018)
Palliative care has had a long-standing commitment to teaching medical students and other medical professionals about pain management, communication, supporting patients in their decisions, and providing compassionate end-of-life care. Palliative care programs also have a critical role in helping patients understand medical conditions, and in supporting them in dealing with pain, fear of dying, and the experiences of the terminal phase of their lives. We applaud their efforts to provide that critical training and fully support their continued important work in meeting the needs of patients and families. Although we appreciate the contributions of palliative care services, we have noted a problem involving some palliative care professionals’ attitudes, methods of decisionmaking, and use of language. In this article we explain these problems by discussing two cases that we encountered.